Synthesis and characterization of a highly stable mucoadhesive gel for oral drug delivery - Shahid, Fatima; Gul, Hashmat; Fareed, Muhammad Amber; Ullah, Faheem; Shafique Satti, Humayoon; Kaleem, Muhammad (Frontiers in Dental Medicine, 2025)
ObjectivesThis study aimed to synthesize and characterize a novel mucoadhesive hydrogel for oral drug delivery, predominantly for the treatment of oral ulcers. Exosomes derived from mesenchymal stem cells were incorporated into the hydrogel with the intention of enhancing the therapeutic effects and minimizing risks such as drug resistance and secondary infections.MethodsA basic hydrogel was synthesized via a combination of hyaluronic acid and carbomer. In addition, various antimicrobial agents were added to produce hydrogel variants. Exosomes were incorporated into the hydrogel variants to create a system for drug delivery. Scanning electron microscopy (SEM), Fourier transform infrared spectroscopy (FTIR), a rheological analysis, mucoadhesive testing, and a swelling and degradation analysis at different pH levels were carried out to characterize the hydrogel. In vitro testing of the basic composition and the hydrogel variants was then carried out, which included a determination of their antimicrobial properties against Escherichia coli, Streptococcus aureus, and Candida albicans, a cytocompatibility analysis via a WST-8 fibroblast quantification assay, and an analysis of exosome release kinetics via UV-Vis spectrophotometry.ResultsThe SEM analysis revealed a porous and interconnected structure within the hydrogel matrix, which is essential for loading drugs. The FTIR spectrum's characteristic peaks confirmed the presence of the constituent polymers. The hydrogel exhibited suitable viscoelastic properties, strong mucoadhesion on bovine mucosa and satisfactory swelling and degradation properties at various pH levels. Effective antimicrobial activity against E. coli, S. aureus, and C. albicans was observed in the study groups in addition to cytocompatibility and an increase in exosome release from the hydrogel with time.ConclusionThis study determined that the exosome-loaded mucoadhesive hydrogel is a promising alternative to traditional oral ulcer treatments. The synthesized hydrogel’s viscoelastic and mucoadhesive behavior, along with its antimicrobial activity and biocompatible nature, suggest that it addresses the challenges in conventional oral ulcer treatment.